2018
DOI: 10.1111/mmi.14143
|View full text |Cite
|
Sign up to set email alerts
|

The small protein MgtS and small RNA MgrR modulate the PitA phosphate symporter to boost intracellular magnesium levels

Abstract: Summary In response to low levels of magnesium (Mg2+), the PhoQP two component system induces the transcription of two convergent genes, one encoding a 31-amino acid protein denoted MgtS and the second encoding a small, regulatory RNA (sRNA) denoted MgrR. Previous studies showed that the MgtS protein interacts with and stabilizes the MgtA Mg2+ importer to increase intracellular Mg2+ levels, while the MgrR sRNA base pairs with the eptB mRNA thus affecting lipopolysaccharide modification. Surprisingly, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…We have shown that the PhoP represses hilA transcription by blocking activation of the promoter and also indirectly affects hilD and rtsA transcription, providing mechanistic insight into how the SPI1 system is shut off after invasion (60). PhoPQ also induces two sRNAs: MgrR and PinT (33,61,62). MgrR regulates genes involved in lipopolysaccharide modification and phosphate import in response to intracellular magnesium levels (61)(62)(63).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…We have shown that the PhoP represses hilA transcription by blocking activation of the promoter and also indirectly affects hilD and rtsA transcription, providing mechanistic insight into how the SPI1 system is shut off after invasion (60). PhoPQ also induces two sRNAs: MgrR and PinT (33,61,62). MgrR regulates genes involved in lipopolysaccharide modification and phosphate import in response to intracellular magnesium levels (61)(62)(63).…”
mentioning
confidence: 93%
“…PhoPQ also induces two sRNAs: MgrR and PinT (33,61,62). MgrR regulates genes involved in lipopolysaccharide modification and phosphate import in response to intracellular magnesium levels (61)(62)(63). The 80-nucleotide (nt) sRNA PinT is produced as a primary transcript, is induced in intracellular Salmonella, and regulates virulence-associated genes (33,44).…”
mentioning
confidence: 99%
“…These regulators have been identified in organisms spanning the phylogenetic tree of life, and important roles have been characterized for small proteins in bacteria and eukaryotes. In Escherichia coli, for example, the absence of the 49 amino acid protein AcrZ renders cells more susceptible to specific antibiotics (4), and cells lacking the 31 amino acid protein MgtS are sensitive to low magnesium concentrations (5,6). In humans and other mammals, the small proteins myoregulin, sarcolipin, and phospholamban regulate muscle activity by affecting calcium transport (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…29 This membranebound SEP also interacts with the PitA cation-phosphate transporter to prevent Mg 2+ export. 47 In contrast, accumulation of Mn 2+ can be toxic to cells. 48 The SEP MntS is repressed by the manganese-dependent transcriptional regulator MntR at high manganese, and overexpression of MntS leads to increased manganese sensitivity.…”
Section: Nutrient Sensing and Utilizationmentioning
confidence: 99%